2009
DOI: 10.1089/jpm.2009.0036
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Patterns of Care for Pancreatic Cancer

Abstract: Introduction: The small proportion of cancers diagnosed at the local disease stage, resectable at the time diagnosis, and responsive to chemotherapy contribute to poor survival making pancreatic cancer the fourth leading cause of cancer death among Americans. This emphasizes the importance of receiving appropriate palliative care. Racial=ethnic cancer treatment disparities have been observed for many cancer sites. We examine patterns of care in a population-based sample of African American, Hispanic and non-Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 20 publications
4
35
1
Order By: Relevance
“…Our data clearly show that only 19% of blacks and 14.5% Hispanics received radiation treatment compared to 22% whites and 25% Asians. These data are in agreement with a previously reported study in which radiation was received by only 15.5 and 16.4% of Hispanics and blacks, respectively (Shavers et al 2009). Previous studies have shown that when the data are controlled for receiving resection for cancer, the outcome is similar and is irrespective of the patient's race (Murphy et al 2009).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our data clearly show that only 19% of blacks and 14.5% Hispanics received radiation treatment compared to 22% whites and 25% Asians. These data are in agreement with a previously reported study in which radiation was received by only 15.5 and 16.4% of Hispanics and blacks, respectively (Shavers et al 2009). Previous studies have shown that when the data are controlled for receiving resection for cancer, the outcome is similar and is irrespective of the patient's race (Murphy et al 2009).…”
Section: Discussionsupporting
confidence: 94%
“…These Wndings are similar to SEER-based study including cases from 1998 (Shavers et al 2009). Overall, the cancer was more common in women with the proportion of women being higher for blacks and Hispanics.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Appropriate treatment is known to be one of the most important predictors of survival in AML (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Differences in receipt of appropriate or evidence-based treatment by race and ethnicity correlate with worse outcomes from several solid malignancies (12,17,18).…”
Section: Introductionmentioning
confidence: 99%